Scrum Framework: Efficiency in Software Projects - da Silva, Edson Coutinho (2016)
Scrum is a framework whose members getting work together as integrated team, with each member is performing a specific function as a self-management team to cut out unnecessary, unappropriated and bureaucratic controls and focus on the essential, which is development processes of systems or software. Thus, Scrum arises as an option, mainly for software organisations. This paper aims to understand how a specific information technology enterprise located in São Paulo (capital) are applying Scrum to manage its softwares projects. Regarding to methodology, this study was defined as a exploratory and action research; we carry out five interviews with professionals who develop the main Scrum functions at this organisation; and a qualitative analysis was applied to understand of best way the data of this research. We recognise that Scrum is a framework and not a process for developing systems; and is oriented to people and not technology. Nevertheless, the PMBoK Guide practices may be complementary the Scrum, even the goals are distinct.